Depth integrated nitrogen fixation from the northern Benguela upwelling system during Maria S. Merain cruise MSM18/4 - Wasmund, Norbert (PANGAEA, 2015)
Nitrogen fixation data from the cruise number MSM18/4 with research vessel "Maria S. Merian" from 24.07.-20.08.2011 (from Libreville to Walvis Bay) in front of Angola and northern Namibia. Samples taken by CTD- rosette sampler from different depths and incubated in glass bottles (535 ml) at light intensities that resemble the in situ light intensities of the sampling depth after Delta 15 N2 gas was injected to the sample. After the incubation time of 6 hours, the complete bottle content was filtered onto a pre-combusted Whatman GF/F filter. Filters were frozen, transported to the institute on dry ice and measured in a mass spectrometer for Delta15N. The principle of the method was described by Montoya et al. (1996) and calculation was done according to their spread sheet. From the data of the single depths, the nitrogen fixation per square meter within the upper 40 m of the water column was calculated. The methods are described in detail in a paper submitted by Wasmund et al. in 2014 to be printed in 2015. Some results are surprisingly below zero. This occurs if the Delta15N of the blank is higher than the measurement after incubation. It indicates that no nitrogen fixation occurred. Due to natural variability, the variability of the nitrogen fixation data is high. In an overall estimate, also over several cruises, negative and positive values compensate more or less, suggesting that nitrogen fixation is insignificant in the waters in front of northern Namibia and southern Angola.